Techno-Economic Environmental and Social (TEES) Potential Assessment of Mega-Scale Grid-Connected Floating PV Power Plants in Five Climate Zones of Pakistan - Amna Mumtaz (00000328420); Dr. Syed Ali Abbas Kazmi (USPCAS-E, NUST, Islamabad, 2022)
TH-377
Keywords: MS-EEP Thesis MS Thesis